Oryginalność Komisji Edukacji Narodowej na tle europejskim - Bartnicka, Kalina (Biuletyn Historii Wychowania, 2015)
The uniqueness of the Commission of National Education in Europe As a result of the ban imposed on the Society of Jesus, post-Jesuit schools and funds had to be submitted to control. On 14 October 1773, on the initiative of king Stanisław August Poniatowski, the Commission of National Education (KEN) was appointed during a session of the parliament confirming the First Partition of Poland. The Commission was a body supervising the entire Polish education system, as well as an education fund created from the post-Jesuit assets. The king and the members of Parliament hoped that the Commission would reform the Polish education system and subsequently Poland would become a powerful state again. The Commission was a state institution appointed by parliament and answerable only to parliament. The Commission members included well-educated individuals, prominent politicians, representatives of the social elite who added to the Commission of National Education’s prestige. The school reform was inspired by the concepts of physiocracy (adapted to Polish conditions), the achievements of the pedagogy and philosophy of the Enlightenment, coupled with the local political and educational heritage, as well as the experiences of the National Academy in educating teachers and in cooperating with secondary schools. The Commission of National Education did not have any examples to follow, be it for institutional work or the planned school reform. The Commission managed to create a new type of state institution in charge of education. University-level education was provided to teachers, while the universities themselves were upgraded in terms of academic requirements and organisation. Departments were replaced with two equal-rank colleges. A Moral College was established with social science and humanities in mind, while a Physical College was created with mathematics and natural science in mind. The universities were delegated the responsibility of academic and pedagogic supervision of secondary schools. The Commission established the modern profession of teacher, the so-called academic estate. Polish was introduced to schools as a teaching language, accompanied by an encyclopaedic curriculum. Polish school books were developed. An enlightened and responsible nobleman-cum-patriot was offered as an educational model. The Laws of the Commission of National Education for the academic estate and the schools of the Polish Republic, an academic legal code, was developed and published in 1783. The Commission was appointed by parliament and had an educational fund at its sole disposal. It was esponsible only to parliament for its activity and financial policy. This significantly differentiated the KEN from the institutions supervising education in Russia, Germany or Austria, as well as other countries, which were financially and legally dependent on enlightened monarchs. The KEN schools educated patriots and citizens, while the schools in absolutist monarchies desired loyal and obedient subjects of the tsar or king.